The scene of lung pathology during PRRSV-1 infection - Ruedas-Torres, Inés; Sánchez-Carvajal, José María; Salguero, Francisco Javier; Pallarés, Francisco José; Carrasco, Librado; Mateu, Enric; Gómez-Laguna, Jaime; Rodríguez-Gómez, Irene Magdalena (Frontiers in Veterinary Science, 2024)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most economically important infectious diseases for the pig industry worldwide. The disease was firstly reported in 1987 and became endemic in many countries. Since then, outbreaks caused by strains of high virulence have been reported several times in Asia, America and Europe. Interstitial pneumonia, microscopically characterised by thickened alveolar septa, is the hallmark lesion of PRRS. However, suppurative bronchopneumonia and proliferative and necrotising pneumonia are also observed, particularly when a virulent strain is involved. This raises the question of whether the infection by certain strains results in an overstimulation of the proinflammatory response and whether there is some degree of correlation between the strain involved and a particular pattern of lung injury. Thus, it is of interest to know how the inflammatory response is modulated in these cases due to the interplay between virus and host factors. This review provides an overview of the macroscopic, microscopic, and molecular pathology of PRRSV-1 strains in the lung, emphasising the differences between strains of different virulence.